Does Distance Matter? Analyzing Distance Decay in Nepal Inbound Tourism - Subedi, Karuna (Journal of Tourism & Adventure, 2025)
The objective of the research is to examine how distance decay concept applies in Nepal’s inbound tourism. To date no previous studies have included Nepal in examining distance decay pattern, nor any study focusing only Nepal has been carried out. Thus, this study utilizes statistics of the Department of immigration to analyze impact of distance on Nepal’s inbound tourism. Applying the concept of Gravity model of tourism, a log-regression analysis is performed to test three hypotheses. The findings of the research reveal that Nepal shows a unique pattern of tourist arrivals where nearest neighbor India is the largest source market. Distance decay curve of Nepal’s inbound tourism aligns with previous studies with the highest peak from immediate land neighbor, then followed by several secondary peaks and ETEZ. However, close and easily accessible market contribute considerably less to Nepal’s tourism. The findings also suggest that GDP of distant source market mitigates negative effect of distance, whereas population size has no statistically significant influence. The outcome of the study is important in the growth of Nepal’s tourism. The results of the study can be utilized by policy makers and tourism stakeholders to attract visitors from the potential source markets.